Geochemical and Sr‐Nd‐Pb‐Fe Isotopic Constraints on the Formation of Fe‐Si Oxyhydroxide Deposits at the Ultraslow‐Spreading Southwest Indian Ridge - Jiangtao Li; Mingxue Sun; Wenlong Qi; Zhe Zhou; Simon V. Hohl; Zhiwei He (Geochemistry, Geophysics, Geosystems, 2024)
Abstract Modern Fe‐Si oxyhydroxide deposits occur in global marine hydrothermal vent sites. Despite their role as biogenic substrates and potential ore resources, much remains unknown about their formation processes. Here, we apply analyses of major and trace elements as well as Sr‐Nd‐Pb‐Fe isotopes combined with 238U‐230Th dating to Fe‐Si oxyhydroxides obtained from several hydrothermal fields along the Southwest Indian Ridge. These mineralized oxyhydroxides primarily consist of poorly crystalline two‐line ferrihydrite and amorphous opal‐A, with lesser amounts of nontronite and birnessite. The ubiquitous and characteristic Fe‐rich ultrastructures in the oxyhydroxides directly indicate microbial activity. The 238U‐230Th dating constrains their crystallization ages from ca. 11,873 to 384 years old. The seawater‐like 87Sr/86Sr and varying 143Nd/144Nd ratios underline a high proportion of seawater mixed with hydrothermal fluids. The radiogenic Pb isotopic patterns suggest a primary derivation of Pb leached from substrate basalts and to a lesser extent Pb from seawater. Stable iron isotopic compositions for different oxyhydroxides display a remarkable range between −1.47 and 0.82‰, which were interpreted as reflecting the fractionation processes during the formation of the deposits under evolving depositional redox conditions. The partial oxidation of Fe(II) and the subsurface removal of isotopically heavy Fe oxyhydroxides are suggested to play a vital role in shifting the Fe isotopic signature toward more negative values. Given that these Fe‐Si oxyhydroxide deposits exhibit features similar to certain ancient iron formations (IFs), Fe isotope systematics of these deposits may hold significant potential for fingerprinting the biological Fe oxidation processes that drove IF deposition on early Earth.